Voluntary associations as schools for democracy? : a case study of the Sibanye Development Project - Siwahla, Lindiwe Lillian (Rhodes University, Faculty of Humanities, Department of Political Studies, 2002)
This is an empirical study of a voluntary association with a view to interrogate the theories of civil society and participation and their practice. These theories came to dominate debate on African politics and democratisation following disappointment with structural approaches to development and democracy. Disenchantment with the state whose role was emphasised by the structural approach led analysts and technocrats to turn their attention to human agency; hence the salience of the idea of popular participation in the public domain, and preoccupation with the idea of strengthening civil society. This trend gained momentum after the 1989 fall of the Berlin Wall and demise of the communist block, and was accompanied by anti-statist sentiments on a global scale. Civil society organisations are seen as schools for democracy and agents of democratic consolidation, and are accordingly expected to perform two major tasks, namely instilling and disseminating a democratic political culture in and among participants and society at large, and promoting good governance. The aim therefore is to take advantage of the supposed intrinsic and utilitarian benefits of participation. As evident in a number of policy documents and legislation, the incumbent South African government embraces the idea of participatory democracy. However, not all analysts share this confidence in the capacity of civil society to perform these tasks. For some analysts public participation does not always have positive intrinsic benefits. Public participation may instead lead to a corrupted political culture deriving from the participants' attempts to survive in a public sphere characterised by manipulation and subtle political control, and it is civil society organisations lacking in organisational strength that are particularly vulnerable. The study revealed that unity between practice and theories of participation and civil society is a complex matter fraught with a number of ambiguities and contradictions. It revealed that though participation in the voluntary association in question does have educative benefits, those benefits do not extend to all the participants. In addition, the quality of that education is contingent upon a number of factors, some internal, others external. The internal and external factors reinforce one another. The internal factors pertain to the organisational dynamics of the voluntary association itself, and the external factors to the nature of the relationship between the voluntary association concerned and public authorities and other civil society organisations.,KMBT_363,Adobe Acrobat 9.54 Paper Capture Plug-in
Keywords: Sibanye Development Project; Non-governmental organizations; Political participation; Non-governmental organizations--South Africa